Penguatan dan Pendampingan Pelaku Usaha Mikro Kecil dan Menengah (UMKM) di Desa Jatimukti, Jatinangor, Sumedang, Jawa Barat - Wulandari, Serly (Civitas Consecratio: Journal of Community Service and Empowerment, 2023)
The packaging design of a product can affect a consumer's psychology because it is the first thing that will be seen. Product packaging design is also one of the special requirements in making a Business License through Online Single Submission (OSS), both the Business Identification Number (NIB) and the Certificate of Fulfillment of Commitments Home Industry Processed Food Production (SPP-IRT). However, a simple product packaging design without a business license is still a feature of the products of Productive MSME players in Jatimukti Village. This service activity aims to provide reinforcement in the form of increasing literacy related to product packaging design and business permits. Then also provide assistance in creating new packaging designs with complete labels and business permits. The business permits in question are in the form of NIB and SPP-IRT which are made through OSS to productive MSME actors in Jatimukti Village. The method of service activities is carried out through FGD with productive MSME in Jatimukti Village, education through socialization and training on product packaging design and business permits. Then there is simulation and assistance to create product packaging designs with complete labels and business permits. This community service activity can be concluded to have a positive impact with the output of the activity in the form of new product packaging designs with complete labels for MSME for Chips and Block Cake products and the issuance of business license in the form of 2 (two) NIB and 3 (three) SPP-IRT.